THE ROLE OF DIGITAL TRANSFORMATION IN ENHANCING EXPENDITURE EFFICIENCY IN PUBLIC UNIVERSITIES: AN EMPIRICAL STUDY - Alkasassbeh, Wasfi Abdulkareem (Veredas do Direito, 2026)
Digital transformation has become a critical driver of efficiency and accountability in public sector organizations, including higher education institutions. This study examines the role of digital transformation in enhancing expenditure efficiency in public universities through an empirical quantitative approach. Data were collected using a structured questionnaire administered to academic and administrative leaders, yielding 178 valid responses. Descriptive and inferential statistical techniques, including correlation and regression analyses, were employed to examine the relationships between digital transformation and expenditure efficiency. The findings indicate that digital transformation, when considered as an integrated organizational capability, has a statistically significant positive effect on expenditure efficiency in public universities. At the dimensional level, systems integration and data interoperability emerge as the most influential predictors of expenditure efficiency, while digital governance, process digitization, and data analytics do not exhibit statistically significant direct effects when examined simultaneously. These results suggest that expenditure efficiency gains in public universities are primarily realized through integrated digital infrastructures rather than isolated digital initiatives. The study contributes to the literature by clarifying the mechanisms through which digital transformation translates into financial efficiency outcomes in the context of public higher education. Practical implications are offered for university leaders and policymakers seeking to improve expenditure efficiency through digital transformation initiatives.